Q. 1 F3.7( 9 Votes )

# <span lang="EN-US

x(x + 4) = 12

x2 + 4x - 12 = 0

x2 + 6x - 2x - 12 = 0

x( x + 6) - 2( x + 6) = 0

(x - 2) (x + 6) = 0

The roots of the equation are those value for which (x - 2) (x + 6) = 0

x = 2 or - 6

2 and - 6 are the roots of the given equation.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses RELATED QUESTIONS :

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics